METODOLOGI PEMBELAJARAN PAIKEM PESANTREN MIZANUL ‘ULUM DUSUN BONTOWA DESA SANROBONE - Nurjannah, Nurjannah; Malia, Agussalim Beddu (Jurnal BALIRESO, 2023)
Learning is said to be effective if it achieves the targets or basic competencies set out in the RPP. The problem is that MTS and MA Pesantren Mizanul Ulum Sanrobone teachers are not yet fully implementing learning methods that show creativity and innovation, which has an impact on maximum learning achievement as well as boredom and motivation. Students take part in learning, especially certain subjects. For this reason, Mizanul Ulum Islamic Boarding School teachers need training in the PAIKEM learning method with a goal Students do not feel bored and fed up, and learning objectives are achieved. The PKM PAIKEM learning methodology aims to train teachers to design models and use training media that are directly practised using game models according to the needs and ages of students. The output of the activity is that all Islamic boarding school teachers teach effective teaching materials with active, innovative, creative and fun learning methods so that students are motivated to learn, not bored with learning. PAIKEM emphasizes positioning teachers as people who create a conducive learning atmosphere or as facilitators in learning so that it is connected interactive dialogue between students and students, students and teachers. The training began with socialization with the Director of Islamic Boarding Schools, Head of Madrasah Aliyah and Head of Madrasah Tsaawiyah; formulate Paikem training materials, carry out training that emphasizes active participants by conveying Paikem theory and practice and the PAIKEM learning model and PkM program evaluation.